Peningkatan Kapasitas Masyarakat dalam Pengendalian Hipertensi melalui Penyuluhan di Kelurahan Poris Gaga Kota Tangerang - Deswita, Reny; Haerani, Beti; Prayogo, Gilang; Putri, Arlinisa Khaira (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
Hypertension is the leading cause of premature death worldwide. Based on the results of a survey in RW 001, Poris Gaga Village to 87 heads of families, hypertension is the disease with the most sufferers (70.7%). The majority of people have insufficient knowledge about hypertension (77%), poor behavior towards hypertension (79.7%), poor attitudes towards hypertension (51.7%), irregular taking of hypertension medication (51.7%). The purpose of this Community Service (PKM) activity is to increase the knowledge and compliance of the community in Poris Gaga Village, Batu Ceper District, Tangerang City Regency regarding the importance of controlling hypertension through an understanding of hypertension and compliance with treatment. The methods used include: lectures, interactive discussions, providing information through educational media in the form of leaflets and measuring aspects related to hypertension through pre-tests and post-tests. The results obtained were an increase in all three aspects, including: good knowledge (72.1%), good attitudes (59.8%), and good behavior (36.8%) regarding hypertension after health education was carried out.